2018
DOI: 10.1161/hypertensionaha.118.11070
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Stimulates Renal Na + and K + Excretion by Inhibiting the K + Channel (Kir4.1) in the Distal Convoluted Tubule

Abstract: Stimulation of BK2R (bradykinin [BK] B2 receptor) has been shown to increase renal Na excretion. The aim of the present study is to explore the role of BK2R in regulating Kir4.1 and NCC (NaCl cotransporter) in the distal convoluted tubule (DCT). Immunohistochemical studies demonstrated that BK2R was highly expressed in both apical and lateral membrane of Kir4.1-positive tubules, such as DCT. Patch-clamp experiments demonstrated that BK inhibited the basolateral 40-pS K channel (a Kir4.1/5.1 heterotetramer) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Furthermore, excess BK can lead to hypokalemia ( Zhang et al, 2018 ), which is associated with arrhythmia and sudden cardiac death ( Kjeldsen, 2010 ), ( Bielecka-Dabrowa et al, 2012 ; Skogestad and Aronsen, 2018 ) , both of which have been reported in COVID-19 patients ( Huang et al, 2020 ; Guo et al, 2020 ), ( Wang et al, 2020 ) ; a recent report confirms that hypokalemia is occurring in severe cases of COVID-19 ( Lippi et al, 2020 ). It is also notable that many of the other symptoms being reported for COVID-19 (myalgia, fatigue, nausea, vomiting, diarrhea, anorexia, headaches, decreased cognitive function) are remarkably similar to other hyper-BK-conditions that lead to vascular hyper-permeabilization such as angioedema as was recently noted ( van de Veerdonk et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, excess BK can lead to hypokalemia ( Zhang et al, 2018 ), which is associated with arrhythmia and sudden cardiac death ( Kjeldsen, 2010 ), ( Bielecka-Dabrowa et al, 2012 ; Skogestad and Aronsen, 2018 ) , both of which have been reported in COVID-19 patients ( Huang et al, 2020 ; Guo et al, 2020 ), ( Wang et al, 2020 ) ; a recent report confirms that hypokalemia is occurring in severe cases of COVID-19 ( Lippi et al, 2020 ). It is also notable that many of the other symptoms being reported for COVID-19 (myalgia, fatigue, nausea, vomiting, diarrhea, anorexia, headaches, decreased cognitive function) are remarkably similar to other hyper-BK-conditions that lead to vascular hyper-permeabilization such as angioedema as was recently noted ( van de Veerdonk et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…The bradykinin storm induced leakage of fluid and hyaluronic acid induced formation of hydrogel into the lungs may be the reason behind low oxygen uptake in severe COVID-19 patients and generation of severe symptoms like hypokalemia associated with arrhythmia and sudden cardiac death. [42][43][44][45] Hence, the drugs which can take care of the bradykinin storm can also be considered as potential therapeutics for COVID-19. SARS-CoV-2 phylogenetic analysis showed that it is meticulously related to two bat-derived SARS-like CoVs (bat-SL-CoVZC45 and bat-SL-CoVZXC21) found in horseshoe bats (Rhinolophus) with ≈89% nucleotide sequence resemblance with bat-SL-CoVZC45.…”
Section: Sars-cov-2 and Covid-19mentioning
confidence: 99%
“…Interestingly, while Kir4.1/5.1 is the sole potassium conductance on the basolateral membrane of the DCT, it coexists with other potassium channels on the basolateral thick ascending limb [113]. This may make the DCT more sensitive to hormonal regulators of Kir4.1/5.1, such as bradykinin or angiotensin II [114,115].…”
Section: Caveats and Alternativesmentioning
confidence: 99%